1996
DOI: 10.1016/0378-1097(96)00223-6
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione is an important antioxidant molecule in the yeast Saccharomyces cerevisiae

Abstract: The tripeptide gamma-L-glutamyl-L-cystinylglycine (glutathione) is one of the major antioxidant molecules of cells and is thought to play a vital role in buffering the cell against reactive oxygen species and toxic electrophiles. We wished to determine the role of glutathione in the protection of the yeast Saccharomyces cerevisiae against oxidative stress. This study shows that glutathione is an important antioxidant molecule in yeast, with gamma-glutamylcysteine synthetase (gsh1) mutants, deficient in glutath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
70
0
5

Year Published

1997
1997
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(75 citation statements)
references
References 10 publications
(12 reference statements)
0
70
0
5
Order By: Relevance
“…Given the importance of glutathione as an antioxidant in eukaryotes and, in particular, in yeast, we wished to investigate the effect of various environmental stresses on the expression of the GSH1 gene (Izawa et al, 1995;Grant et al, 1996b;Stephen and Jamieson, 1996). While we had previously demonstrated that the steady-state levels of the GSH1 mRNA were increased by exposure of cells to oxidants, we needed to demonstrate that this was due to changes in transcription and not through alterations in mRNA stability (Stephen et al, 1995).…”
Section: Transcriptional Regulation Of Gsh1 Gene Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the importance of glutathione as an antioxidant in eukaryotes and, in particular, in yeast, we wished to investigate the effect of various environmental stresses on the expression of the GSH1 gene (Izawa et al, 1995;Grant et al, 1996b;Stephen and Jamieson, 1996). While we had previously demonstrated that the steady-state levels of the GSH1 mRNA were increased by exposure of cells to oxidants, we needed to demonstrate that this was due to changes in transcription and not through alterations in mRNA stability (Stephen et al, 1995).…”
Section: Transcriptional Regulation Of Gsh1 Gene Expressionmentioning
confidence: 99%
“…This molecule can act as a free-radical scavenger, with the redox-active sulphydryl group reacting with oxidants to produce oxidized glutathione (GSSG). Previously, ourselves and others have examined the role of glutathione in protecting S. cerevisiae against oxidative stress and have shown that glutathione is an important antioxidant molecule in this organism (Izawa et al, 1995;Grant et al, 1996b;Stephen and Jamieson, 1996). Cellular glutathione levels have been found to be regulated by a gene involved in conferring resistance towards zinc and cadmium (Kobayashi et al, 1996), but the molecular mechanism has not been established.…”
Section: Introductionmentioning
confidence: 99%
“…Glutathione-deficient mutants have been shown to be hypersensitive to H 2 O 2 , as well as to the superoxide anion generators plumbagin and menadione (Grant et al, 1996;Stephen and Jamieson, 1996). These mutants are also hypersensitive to the heavy metal cadmium, and the expression of the yeast GSH1 gene, involved in glutathione biosynthesis, has been shown to be inducible by cadmium (Glaeser et al, 1991;Kistler et al, 1986;Stephen and Jamieson, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Addition of yeast to tarhana caused an increase in antioxidant activity. The antioxidant activity of the bakers' yeast comes from bioactive compounds which can serve as antioxidants, for example glutathione, Maillard reaction products and sulfur-containing amino acids (Sommer, 1996;Stephen and Jamieson, 1996). 25 % barley bran (28.06%) and 50 % rye flour (27.86%) addition in tarhana showed the highest antioxidant activity.…”
Section: Nutritional Evaluationmentioning
confidence: 99%